Business development with strategic management decision for bank millenial indonesia, tbk - Venato, Graeta; Dung Do, Anh (The Indonesian Journal of Business Administration, 2019)
Abstract - Bank Millennial Indonesia is one the financial institution specialized for commercial business focus. The bank recorded the position in Bank Umum Kegiatan Usaha (BUKU) 3rd category for asset proportion. Bank Millennial Indonesia established on June, 10th 1980. Formerly, the bank known as Indonesian Citizen Bank. In the journey of business, the bank merged with some commercial Bank and changed the name of the Bank from Bank Citizen Indonesia to Bank Millennial Indonesia. The Bank already listed in Indonesian stock exchange with Initial Public Offering on July 2010.  The main focus of Bank is to provide loan product for customer in Usaha Mikro Kecil Menengah (UMKM) and to provide saving and time deposit product for Indonesian Citizen with good interest deposit for the customer. The cost strategy offered with low interest loan and high interest deposit. In one interview, the CEO's explained that the bank should be focusing on loan number proportion in 2019. The bank would be using the bank’s competitive advantage to increase the bank's Net Interest Margin. The target of Loan consumption especially for retail segment and UMKM. In other explanation, the CEO's told that the increasing number of Non-Performing Loan is one of the bank challenges in the following years. The NPL number raised because some of the corporate customers delayed their payment. It potentially increased the percentage of bad debt and NPL ratio. Facing this challenge, the composition of low-interest for Loan and high-interest for deposit should help the bank's staff to attracting more customer and help the bank to facing the challenge. This Final Project included with the bank's internal and external problem analysis and included with the research objective to increase the bank’s profit. This Final Project also contain with strategic improvement planning in the following years especially to reduce NPL number, increase Net Interest Income, and Increase Fee-based income.Keyword: Advertising Product, Non-Performing Loan, Service, Strategy